Instability to nonlinear vector differential equations of fourth order with constant delay - Tunc, Cemil (Universiti Kebangsaan Malaysia, 2013)
We consider a vector nonlinear differential equation of fourth order with a constant delay. We establish new sufficient conditions, which guarantee the instability of the zero solution of that equation. An example is given to illustrate the theoretical analysis made in this paper.